2013
DOI: 10.1128/aem.02767-12
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Genome-Wide Transcriptional Response of Escherichia coli O157:H7 to Cinnamaldehyde Exposure

Abstract: Cinnamaldehyde is a natural antimicrobial that has been found to be effective against many food-borne pathogens, including Escherichia coli O157:H7. Although its antimicrobial effects have been well investigated, limited information is available on its effects at the molecular level. Sublethal treatment at 200 mg/liter cinnamaldehyde inhibited growth of E. coli O157:H7 at 37°C and for <2 h caused cell elongation, but from 2 to 4 h growth resumed and cells reverted to normal length. To understand this transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 57 publications
5
35
0
Order By: Relevance
“…Similarly, cinnamaldehyde at ϳ100 mg/liter downregulates the proteins involved in oxidative stress response in Cronobacter sakazakii (63). Low cinnamon oil concentrations, especially 0.5ϫ MIC, however, increased the oxidative stress response gene expression, which is consistent with a previous report showing that 2 h of cinnamaldehyde (200 mg/liter) exposure caused oxidative stress responses in E. coli O157:H7 (64). Oxidative stress plays a positive role in stx 2 gene expression (65).…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, cinnamaldehyde at ϳ100 mg/liter downregulates the proteins involved in oxidative stress response in Cronobacter sakazakii (63). Low cinnamon oil concentrations, especially 0.5ϫ MIC, however, increased the oxidative stress response gene expression, which is consistent with a previous report showing that 2 h of cinnamaldehyde (200 mg/liter) exposure caused oxidative stress responses in E. coli O157:H7 (64). Oxidative stress plays a positive role in stx 2 gene expression (65).…”
Section: Discussionsupporting
confidence: 89%
“…In comparison, GO and MG treatments had smaller effects on PA2275 transcription levels (17-and 7-fold, respectively) ( Table S3). The PA2275-encoded product shares 40% sequence similarity with YqhD from E. coli, an enzyme promoting the degradation of CNA into the less-toxic cinnamic alcohol (31,37). Altogether, these results corroborate the hypothesis that the transient activation of CmrA by GO, MG, and CNA is due to the rapid degradation of these molecules into metabolites lacking electrophilic properties, via different bacterial enzymes.…”
supporting
confidence: 69%
“…The same negative results were obtained when disulfide stress (diamide) (28), oxidative stress (H 2 O 2 , paraquat, and dimethyl sulfoxide [DMSO]), and nitrosative stress (S-nitrosoglutathione [GSNO] and 2-n-heptyl-4-hydroxyquinoline N-oxide [HQNO]) (29) elicitors were added at subinhibitory concentrations to the bacterial cultures (data not shown). Finally, we found that three CmrA-regulated proteins (PA2048, PA2275, and PA2276) share Ն40% amino acid similarity with E. coli enzymes implicated in the response to electrophilic stress (YgiN, YqhD, and YqhC, respectively) (30,31). This cellular stress is characterized by an imbalance between the formation and the removal of reactive electrophilic species (RES) containing ␣,␤-unsaturated carbonyl (32) or other electrophilic groups (33).…”
mentioning
confidence: 99%
“…In most cases, the extent of toxicity seems to depend on the aldehyde but may also depend on the choice of microorganism. Cinnamaldehyde, for example, is known to be a potent antimicrobial (74). In the case of vanillin, Zaldivar et al found that 1.5 g/liter of vanillin completely inhibited growth of the E. coli strains examined (73).…”
Section: Addressing Aldehyde Toxicitymentioning
confidence: 99%